Effect of green trade barriers on export enterprise green technological innovation from the perspective of the low-carbon city pilot policy - Xu, Pei; Jin, Zehu; Wu, Xianghua (Frontiers in Environmental Science, 2024)
The low-carbon city pilot policy (LCCPP) is an important part of achieving “dual carbon” goals and promoting green technology innovation (GTI) in Chinese export enterprises. This study integrates Green Technical Barriers to Trade (GTBTs), LCCPP, and the GTI of exporting enterprises into a unified framework based on data from A-share market Chinese non-financial export enterprises from 2007 to 2021 and discusses how export enterprises should optimize green innovation resource structure with support from LCCPP to facilitate enterprise GTI when facing GTBTs. Several findings are uncovered: (1) GTBTs have a significant negative impact on the GTI of Chinese export enterprises, and the LCCPP significantly mitigates the negative impact of GTBTs on export enterprises’ GTI. (2) After distinguishing the heterogeneous characteristics of export enterprises, the moderating effect of the LCCPP becomes even more pronounced in non-state-owned enterprises, general trade enterprises, and enterprises whose export destinations are high-income countries. (3) Further exploration of the moderating effect of the LCCPP with different policy instruments and intensities is needed. We found the best moderating effect on export enterprises’ GTI under high policy intensity, and only market-based policy instruments had a significant moderating effect. These findings provide direction for policymakers expanding the pilot scope of low-carbon cities as well as theoretical support for realizing foreign trade growth for sustainable development.